2017
DOI: 10.1038/srep41282
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene response pathway modulates attractiveness of plant roots to soybean cyst nematode Heterodera glycines

Abstract: Plant parasitic nematodes respond to root exudates to locate their host roots. In our studies second stage juveniles of Heterodera glycines, the soybean cyst nematode (SCN), quickly migrated to soybean roots in Pluronic F-127 gel. Roots of soybean and non-host Arabidopsis treated with the ethylene (ET)-synthesis inhibitor aminoethoxyvinylglycine (AVG) were more attractive to SCN than untreated roots, and significantly more nematodes penetrated into roots. Moreover, Arabidopsis ET insensitive mutants (ein2, ein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 67 publications
(89 reference statements)
3
39
1
1
Order By: Relevance
“…Our data indicate that M. incognita and G. pallida regulate their behaviour ex planta in response to ERF-E2, but not ERF-E3. This corroborates our hypothesis that one or more ERF gene products regulate root exudate composition, phenocopying the enhanced attraction of PPNs observed following the inhibition of ethylene synthesis (Hu et al, 2017;Fudali et al, 2013). Our data also demonstrate that M. incognita and G. pallida use developmentally regulated signalling processes in the host plant to coordinate host selection behaviour ex planta.…”
Section: Moneymakersupporting
confidence: 88%
See 2 more Smart Citations
“…Our data indicate that M. incognita and G. pallida regulate their behaviour ex planta in response to ERF-E2, but not ERF-E3. This corroborates our hypothesis that one or more ERF gene products regulate root exudate composition, phenocopying the enhanced attraction of PPNs observed following the inhibition of ethylene synthesis (Hu et al, 2017;Fudali et al, 2013). Our data also demonstrate that M. incognita and G. pallida use developmentally regulated signalling processes in the host plant to coordinate host selection behaviour ex planta.…”
Section: Moneymakersupporting
confidence: 88%
“…For this line of research to develop robust and durable new sources of PPN resistance, it will be important to establish the behavioural impact that such interventions have on geographically coincident species, as well as different populations of a given species (Cox et al, 2019b). Nonetheless, our data indicate that ERF-E2 knockdown phenocopies the enhanced attraction of certain PPN species, which is also observed following the inhibition of ethylene signalling (Hu et al, 2017;Fudali et al, 2013). It is possible that other ERF genes contribute to this interaction (positively or negatively), which necessitates further investigation.…”
Section: Moneymakermentioning
confidence: 80%
See 1 more Smart Citation
“…Chemical and genetic manipulations of ethylene biosynthesis in Arabidopsis and tomato have shown that ethylene biosynthesis is required for susceptibility to rootknot and cyst nematodes (Glazer et al, 1985;Goverse et al, 2000;Wubben et al, 2001). Arabidopsis mutants deficient in ethylene signalling are more attractive to infective cyst nematodes and root-knot nematodes (Fudali et al, 2013;Hu et al, 2017). However, giant cells induced by M. javanica in tomato plants treated with an inhibitor of ethylene biosynthesis [aminoethoxyvinylglycine (AVG)] show significantly reduced cellular hypertrophy (Glazer et al, 1985).…”
Section: Ethylene Biosynthesis and Signalling In Nematode-induced Feementioning
confidence: 99%
“…Roots of soybean and Arabidopsis treated with ethylene synthesis inhibitor attracted more Soybean cyst nematodes (Heterodera glycines), and significantly more nematodes penetrated the roots of ethylene synthesis inhibited plants. On the other hand, ethylene insensitive mutants roots of Arabidopsis accessions were more attractive to H. glycines than the wild type (Hu et al, 2017). Ethylene-overproducing A. thaliana mutants roots were hypersusceptible to beet cyst nematode (Heterodera schachtii), and ethylene-insensitive mutants were less susceptible to H. schachtii (Wubben et al, 2001).…”
Section: Repellantsmentioning
confidence: 99%